RISK MANAGEMENT: SAFE WORK CULTURE IN MANUFACTURING INDUSTRY - Khairunnisa’ Binti Yussof; Siti Musliha Binti Mohd Idris; Mastura Binti Ayob; Norfaezah Binti Mohd Shahren (International Journal of Accounting, Finance and Business, 2021)
Accidents that occur within an organisation impact both employers and employees. This impact is in the form of costs and lost profit to the employers. Normally, the cost of accidents could be considered as higher than expected because they involve hidden or indirect costs. This will affect the way they work. A safe work culture needs more attention since it could influence the business to give significant attention to the operational and financial impact for the employers’ business. Employees who are involved in accidents will suffer lost income. Therefore, the rate of accidents could be reduced by implementing the right risk management control. Enterprise-wide risk management (EWRM) is one of the examples of risk management. This risk management is more reliable since it could cover the risks holistically compared with traditional risk management, where risk is managed or handled individually. One of the foundations of EWRM is identifying a safe work culture. The reason is to inform entities in the department or working place of the correct or incorrect way since it’s related to norms and values that are possessed by the organisation. The aim of this study to identify the relationship between strategic communication, leadership roles, organisational design, and employee engagement towards a safe work culture. This study used stratified sampling and distributed questionnaires to 379 respondents. The findings showed that all the variables had significant relationships to safe work culture. This outcome will be used as guidelines for manufacturers to evaluate the manufacturing environment as well as helping them to enhance their productivity and success in EWRM implementation.